2021
DOI: 10.1108/cg-03-2021-0119
|View full text |Cite
|
Sign up to set email alerts
|

Stock liquidity and stock return: an asymmetric impact of institutional ownership approach

Abstract: Purpose This study is primarily aimed at investigating the asymmetric impact of institutional ownership on the relationship between stock liquidity and stock return. It was conducted by testing the hypotheses regarding efficient monitoring and adverse selection from Tehran Stock Exchange (TSE). Design/methodology/approach Using a panel smooth transition regression model and selecting 183 firms for the period from 2009 to 2019 from TSE, this study examined the data to explore the asymmetric impact of institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 81 publications
(153 reference statements)
0
5
0
Order By: Relevance
“…In the first regime, the performance increases with institutional ownership until a threshold level of ownership and then decreases in the second regime. Daryaei and Fattahi (2022) find a positive impact of institutional investors on stock liquidity and returns for moderate levels of institutional ownership (less than 40%) and a negative impact for high levels of ownership. Gharbi and Othmani (2022) find that the relationship between family ownership and financial performance is characterised by a threshold effect.…”
Section: Methodsmentioning
confidence: 83%
“…In the first regime, the performance increases with institutional ownership until a threshold level of ownership and then decreases in the second regime. Daryaei and Fattahi (2022) find a positive impact of institutional investors on stock liquidity and returns for moderate levels of institutional ownership (less than 40%) and a negative impact for high levels of ownership. Gharbi and Othmani (2022) find that the relationship between family ownership and financial performance is characterised by a threshold effect.…”
Section: Methodsmentioning
confidence: 83%
“…On the other hand, studies by Wang (2022);De Cesari et al (2012), and Daryaei and Fattahi (2022) have found a negative relationship between the ratio of institutional ownership structure and equity liquidity. These studies interpret this as evidence that institutional investments are short-term and for speculative purposes, meaning that institutions deal as speculators rather than owners.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 97%
“…While the size of a corporation can affect its value, but this effect is not directional. Nonetheless, studies by Natsir and Yusbardini (2020); Widnyana, Astiti, and Suarjana (2021); Zuhroh (2019) and Daryaei and Fattahi (2022) have found a positive relationship of the size of the corporation on corporation value. However, other studies (Hirdinis, 2019;Niresh & Thirunavukkarasu, 2014) suggest that there is a negative relationship between the size of the corporation and its corporation value.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 98%
See 1 more Smart Citation
“…Equally important, as evidenced by Daryaei and Fattahi (2022), with an increase in institutional ownership up to a certain level, the relationship between liquidity and stock returns strengthens. However, when institutional ownership exceeds a certain level, its further increase results in a weakening of the liquidity-return relationship.…”
Section: Hypothesis Developmentmentioning
confidence: 97%